FOREST ECOSYSTEM SERVICE UTILIZATION TO INCREASE HUMAN HEALTH: FOREST THERAPY TRIALS IN TAMAN HUTAN RAYA IR DJUANDA - Emmelinda Satyawan, Verda; Rusdiana, Omo; Latifah, Melly (Indonesian Journal of Forestry Research, 2025)
Forest therapy is an activity used to obtain health benefits from forest environmental services. This research conducted a systematic literature review, constructed a forest therapy program based on said literature review, and experimented on how the forest therapy program affects human health. The forest therapy program was experimented with in "Ir. H. Djuanda Forest Park (Tahura Djuanda)" in Bandung, West Java, Indonesia. This research also analyzed forest characteristics: temperature, humidity, light intensity, and noise levels. The forest therapy program developed consists of stretching, walking in the forest, forest sensing, and consuming boiled sweet potatoes and warm tea. The temperature of the area ranged from 22 to 25.6°C, with humidity ranging from 61% to 87%. Light intensity ranged from 291 lux to 970 lux and noise levels ranged from 49 dB to 52.5 dB. The forest therapy program, which involved 30 participants, demonstrated a notable impact on reducing pulse rate and alleviating negative emotion (mood), suggesting its effectiveness in fostering both psychological and physiological relaxation. However, the findings also revealed a decrease in oxygen saturation, which contradicts the expected outcome following a forest therapy program. Further research is needed regarding the precise mechanisms through which individuals derive therapeutic benefits from natural interventions. It is also important to experiment with a diverse sample size and characteristics of participants. Additionally, it is also crucial to conduct a study on the economic value of forest therapy as a business opportunity in Indonesian conservation areas.